Baseline Asymptomatic Malaria Infection and Immunogenicity of Recombinant Vesicular Stomatitis Virus–Zaire Ebola Virus Envelope Glycoprotein: Vaccine: The Sierra Leone Trial to Introduce a Vaccine Against Ebola (STRIVE). (20th May 2021) - Mahon, Barbara E; Simon, Jakub; Widdowson, Marc-Alain; Samai, Mohamed; Rogier, Eric; Legardy-Williams, Jennifer; Liu, Kenneth; Schiffer, Jarad; Lange, James; DeByle, Carolynn; Pinner, Robert; Schuchat, Anne; et al.
Abstract: Background: The effect of malaria infection on the immunogenicity of the recombinant vesicular stomatitis virus–Zaire Ebola virus envelope glycoprotein (GP) vaccine (rVSVΔG-ZEBOV-GP) (ERVEBO) is unknown. Methods: The Sierra Leone Trial to Introduce a Vaccine Against Ebola (STRIVE) vaccinated 7998 asymptomatic adults with rVSVΔG-ZEBOV-GP during the 2014–2016 Ebola epidemic. In STRIVE's immunogenicity substudy, participants provided blood samples at baseline and at 1, 6, and 9–12 months. Anti-GP binding and neutralizing antibodies were measured using validated assays. Baseline samples were tested for malaria parasites by polymerase chain reaction. Results: Overall, 506 participants enrolled in the immunogenicity substudy and had ≥1 postvaccination antibody titer. Of 499 participants with a result, baseline malaria parasitemia was detected in 73 (14.6%). All GP enzyme-linked immunosorbent assay (ELISA) and plaque reduction neutralization test (PRNT) geometric mean titers (GMTs) at 1, 6, and 9–12 months were above baseline, and 94.1% of participants showed seroresponse by GP-ELISA (≥2-fold rise and ≥200 ELISA units/mL), while 81.5% showed seroresponse by PRNT (≥4-fold rise) at ≥1 postvaccination assessment. In participants with baseline malaria parasitemia, the PRNT seroresponse proportion was lower, while PRNT GMTs and GP-ELISA seroresponse and GMTs showed a trend toward lower responses at 6 and 9–12 months. Conclusion: Asymptomatic adults with or without malaria parasitemia had robust immune responses to rVSVΔG-ZEBOV-GP, persisting for 9–12 months. Responses in those with malaria parasitemia were somewhat lower. Abstract : We assessed the immunogenicity of recombinant vesicular stomatitis virus–Zaire Ebola virus envelope glycoprotein vaccine in Sierra Leone adults with or without asymptomatic malaria parasitemia. A robust immune response persisted for 9–12 months in both study groups. Responses in participants with asymptomatic malaria parasitemia were somewhat lower.